Early Effects of Treatment Low-Dose Atorvastatin on Markers of Insulin Resistance and Inflammation in Patients with Myocardial Infarction - Gruzdeva, Olga; Uchasova, Evgenya; Dyleva, Yulia; Akbasheva, Olga; Karetnikova, Victoria; Barbarash, Olga (Frontiers in Pharmacology, 2016)
Dyslipidemia is one of the primary causes of cardiovascular disease. Therefore, attention has been focused on the development of drugs that normalize lipid levels and exert an effect on markers of atherothrombosis, insulin resistance (IR), and inflammation. Atorvastatin is a drug with not only lipid-lowering potential, but it has multiple non-lipid effects. This study aimed to evaluate atorvastatin effects on lipid, adipokine, IR and inflammatory statuses in patients with myocardial infarction (MI) in an in-hospital setting. This study included 90 patients with confirmed ST-segment elevation MI, who were treated with atorvastatin 20 mg/day starting on day 1 of MI, without any dose changes. The comparison group consisted of 89 patients receiving standard anti-anginal and anti-thrombotic therapy. During the hospital stay, both groups showed a reduction in total cholesterol level and free fatty acids and increased concentrations of apolipoprotein A, especially those patients receiving atorvastatin. On day 1 of MI, patients in both groups had elevated levels of leptin by 2.9- to 3.3-fold, but the leptin levels decreased by 40.3% and were significantly lower than in patients not taking statins. The treatment with atorvastatin was associated with a decrease in C-reactive protein and interleukin-6 by 23.1% and 49.2%, respectively, compared with baseline values. In the group of patients on standard therapy, there was a decrease of interleukin-6 by 31.7%. Atorvastatin administered early on during hospitalization to patients with MI contributed to the improvement of lipid, adipokine and pro-inflammatory statuses and decreased IR.